El libro de Fenggang Yang, Religion in China. Survival & Revival under Communist Rule - Martínez Esquivel, Ricardo (2015)
The author makes a critical reading of the book Religion in China. Survival & Revival under Communist Rule by the Chinese specialist Fenggang Yang (published in 2012) during the government of Mao Zedong and the Chinese Communist Party and their process of secularization by means of atheism.